Digitalisation in Education: Language Learning Motivation Booster - Raihana Ahmad Jalaluddin,; Chan Mei Ki, (Development in Language Studies, 2024)
Integrating digital technology into tertiary education has become imperative, necessitating an in-depth exploration of its impact on students’ motivation, especially to learn English. This research investigates the intricate relationship between digitalisation and student motivation to learn the language among tertiary students in Petaling District, Malaysia. Utilizing a quantitative approach, the researcher conducted surveys with 272 participants, adhering to the recommended sample-to-item ratio of 5:1. The predictive survey research design enabled researchers to anticipate future trends in this dynamic context. The findings reveal that digitalisation significantly influences students’ motivation in language learning. The study highlights the role of educational institutions in fostering a digitally enriched learning environment that promotes student’s engagement and motivation while learning the language. This research contributes valuable insights to the broader discourse on technology-enhanced education, offering practical recommendations for educators and policymakers to optimize digitalisation's impact on student motivation to learn the English language in a diverse educational landscape.